ANALISIS PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN PENGEMBANGAN KARYAWAN SEBAGAI VARIABEL INTERVENING (Studi pada PT Perkebunan Nusantara IX Divisi Tanaman Tahunan) - Miswari, Haikal; Mas’ud, Fuad (Diponegoro Journal of Management, 2017)
This research was conducted at PT Perkebunan Nusantara IX Divisi Tanaman Tahunan by existence of decrease in employee performance, and supported research gaps that showed different results. So, the purpose of this research is to determine the influence of organizational culture on employee performane through employee development. Data was collected through questionnares to 53 employees with sensus method. The techniques of data analysis in this research includes the test of validity, reliability, classical assumptions, multiple regression, and sobel test to examine the mediation effect. The results analysis and discussion indicates that organizational culture culture have positive and significant effect on employee performance, employee development have positive and significant effect on employee performance. Furthermore, employee development is provenn as mediator relathionship between organizational culture on employee performance.